Where$1 (Bs Chimpy? s - Rabe, Berniece; Schmidt, Diane (Niles, Ill. : A. Whitman, 1988)
Text and photographs show Misty, a little girl with Down$1 (Bs syndrome, and her father reviewing her day$1 (Bs activities in their search for her stuffed monkey.s
Keywords: Down syndrome -- Fiction; People with mental disabilities -- Fiction; Lost and found possessions -- Fiction